Direct in vitro organogenesis from leaf and internode of Coccinia cordifolia (L.) Cogn. - Sarkar, Md. Taufiqur Rahman; Rahman, Md. Mizanur; Alam, Mohammad Firoz (Horticultural Biotechnology Research, 2022)
The current study was carried out to elucidate a reproducible protocol to develop plants directly from leaf and internodes to facilitate the genetic transformation in Coccinia cordifolia (L.) Cogn., a medicinal plant of the cucurbitaceae family. In vitro grown leaf and internodes were used, which were collected for regenerated shoots from field-grown nodal segments that were sterilized by 0.1% HgCl2 treatment for 6 minutes. The nodal segment cultured on BAP, Kn and BAP, NAA combination where 1.5 mg/L BAP solitary supplement and augmented supplement with 0.1 mg/L NAA was most effective as 80% shoots regenerated with 4.0±0.37 and 2.7±0.45 shoots per culture, respectively. Collected leaf and internode responded 90% at 1.5 mg/L BAP + 0.1 mg/L NAA fortified full-strength MS medium. The highest number of shoots also regenerated in the same combination which were 8.1 ± 0.30 and 10.2±0.40, respectively and found internode as the best explant for direct organogenesis. For root induction, half strength of MS medium supplemented with 0.1 mg/L IBA was found most effective. The highest number of roots regenerated per shoot (6.8±0.10) and root length (2.8±0.20). The successful acclimatization of the in vitro (80%) grown plantlets proved the validity of the developed protocol of using biotechnological techniques for improving the plant.